Once more with passion Filipino women and politics - Tapales, Proserpina D. (2016)
Throughout history, the Filipino women had been taking part in the shaping of Philippine politics. Women in precolonial\ Philippines were regarded highly and were given key political roles. They participated in the revolutionary and resistance movements against the Spanish, American and Japanese colonial regimes. In contemporary Philippine politics, the number of Filipino women who are holding elective positions in the national and local level of the government is increasing. In post-Martial Law era, women's political parties have been participating in the national elections. Some elected women officials have used their influence and position to advance women's causes by enacting laws that uphold and protect the rights and welfare of women. However, the increased participation and representation of women in politics can be attributed to dynastic politics of the Philippines. To skirt around term limits on elective positions, close relatives of the incumbent, mostly the wife and offspring, are fielded to run in the elections to continue the political family's hold on power. In the context of dynastic politics in the Philippines, women's participation and representation in politics and decision making in government should not alone be measured by the number of women in elective positions. Rather, it should be seen in the elected official's ability to advance the rights and causes of women as a sector of the society.
Keywords: Women in politics; Social conditions of women; Women -- Equal rights; Women -- Politics and government